Art work invisible labour and the legacy of Yugoslav socialism - Praznik, Katja 1978- (University of Toronto Press, 2021)
By exposing the separation of art and labour, Art Work provides a valuable, historical perspective on the present-day struggle for artists' rights.
Keywords: Geschichte; EDUCATION / General; African American children -- Education -- Illinois -- Chicago -- History; High school graduates -- Illinois -- Chicago; Public schools -- Illinois -- Chicago -- History; School integration -- Illinois -- Chicago -- History; Sozialismus; Politik; Arbeit; Künstler; Kunst; Jugoslawien; Electronic books